Application of Chiral Sulfinamides into Formation and Reduction of Sulfinylketimines to Obtain Valuable α‐Chiral Primary Amines. Issue 37 (17th July 2020) - Achuenu, Chukuka; Carret, Sébastien; Poisson, Jean‐François; Berthiol, Florian
Abstract : Chiral sulfinamides are very valuable, commercially available, and easy to handle chiral auxiliaries. One of the most interesting transformations that can be performed with a chiral sulfinamide is its condensation onto a ketone to form a chiral sulfinylketimine, followed by a reduction to obtain an α‐chiral primary amine. We review here all the methodologies developed around this condensation/reduction transformation. In the second part, we survey applications of these newly developed methodologies for the synthesis of valuable biologically active compounds, including multikilogram scale synthesis. Abstract : This minireview focuses on the use of sulfinamides as chiral auxiliaries in a condensation/reduction process to give access to α‐chiral primary amines. This paper gives an overview of all the methodologies developed around this process including metal hydride and transition metal reduction reactions, and of the application of these methodologies for the synthesis of valuable biologically active chiral compounds.